Health and performance challenges during sports training and competition in cold weather - Castellani, J. W.; Young, A. J. (British Journal of Sports Medicine, 2012)
Olympic athletes compete and train in diverse cold-weather environments, generally without adverse effects. However, the nature of some sports may increase the risk of cold injuries. This paper provides guidance to enable competition organisers and officials, coaches and athletes to avoid cold-weather injuries. This paper will (1) define potential cold-weather injuries during training and competition and (2) provide risk management guidance to mitigate susceptibility to cold-weather injuries.